2018
DOI: 10.3390/nu10111780
|View full text |Cite
|
Sign up to set email alerts
|

Regular Practice of Moderate Physical Activity by Older Adults Ameliorates Their Anti-Inflammatory Status

Abstract: A chronic inflammatory state is a major characteristic of the aging process, and physical activity is proposed as a key component for healthy aging. Our aim was to evaluate the body composition, hypertension, lipid profile, and inflammatory status of older adults, and these factors’ association with physical activity. A total of 116 elderly volunteers were categorized into terciles of quantitative metabolic equivalents of task (MET). Subjects in the first and third terciles were defined as sedentary and active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 57 publications
4
25
0
Order By: Relevance
“…According to the study by Ferrer et al [71] with 116 elderly volunteers, through physical activity there is a decrease in the current levels of IL-6, as well as an increase in the expression of IL-10 in active individuals [71]. A low presence of circulating pro-inflammatory cytokines is observed in contrast to the increase in anti-inflammatory cytokines.…”
Section: Physical Exercise and Covid-19mentioning
confidence: 99%
“…According to the study by Ferrer et al [71] with 116 elderly volunteers, through physical activity there is a decrease in the current levels of IL-6, as well as an increase in the expression of IL-10 in active individuals [71]. A low presence of circulating pro-inflammatory cytokines is observed in contrast to the increase in anti-inflammatory cytokines.…”
Section: Physical Exercise and Covid-19mentioning
confidence: 99%
“…Skeletal muscle is a major immunoregulatory organ and produces a range of soluble factors, which have anti-inflammatory and immunoprotective effects [41]. Indeed, regular exercise improves physical capacity and muscle mass and function and reduces cardiometabolic risk factors and systemic inflammation in older adults [42]. Physically active older adults have lower concentrations of circulating proinflammatory biomarkers, and higher concentrations of anti-inflammatory cytokines, compared to physically inactive individuals, and this is partly due to muscle physiology [42].…”
Section: Immunosenescence As a Modifiable Risk Factor For Covid-19?mentioning
confidence: 99%
“…Indeed, regular exercise improves physical capacity and muscle mass and function and reduces cardiometabolic risk factors and systemic inflammation in older adults [42]. Physically active older adults have lower concentrations of circulating proinflammatory biomarkers, and higher concentrations of anti-inflammatory cytokines, compared to physically inactive individuals, and this is partly due to muscle physiology [42]. Indeed, muscle contraction triggers an anti-inflammatory response by releasing so-called "myokines" -muscle-secreted factors that influence almost all aspects of physiology and metabolism [43].…”
Section: Immunosenescence As a Modifiable Risk Factor For Covid-19?mentioning
confidence: 99%
“…In an attempt to minimize the imbalance of both inflammation and oxidative stress associated with aging, some nonpharmacological interventions, such as nutritional care and regular practice of physical exercises, are well accepted and largely recommended. Indeed, it has been demonstrated that the moderate exercise training has beneficial effects on the systemic inflammatory response in elderly individuals, not only by reducing proinflammatory cytokines, as TNF-α, IL-1β, and IL-6 [9] but also by increasing the circulating levels of IL-10, a classic anti-inflammatory cytokine [10,11]. Noteworthy, the American College of Sports Medicine (ACSM) states that training programs must contain combined exercises (endurance and resistance) for maximum benefits in human health, by optimizing cardiovascular, respiratory, immune, and muscle functions.…”
Section: Introductionmentioning
confidence: 99%